Piping hot dogs: A case of a Malaysian franchise - June, Sethela; Abdul Talib, Asmat Nizam (Emerald Group Publishing Limited, 2011)
This case is about a newly established fast food company that expands very rapidly in Malaysia. Growing from merely a single pushcart, the company has evolved into one of the most successful purely-local food franchise businesses with almost 100 franchises throughout the country and abroad. The company keeps on looking at bigger expansion plans abroad and eyeing the Middle Eastern markets. Expected learning outcomes – After carrying out this exercise, students are expected to be able: to understand how a new business start up grows; to provide a simple illustration on how internationalization of small firms can took place; to analyze the various factors of considerations prior to internationalization; to identify the basic issues of international franchising and how the system works.